The Impact of Cost Control Strategies on the Performance of Youth Owned Small and Medium Enterprises in Ethiopia: A Literature Review - Habetie, Tadesse Getachew; Kolta, Dóra; Prihoda, Emese (Acta Carolus Robertus, 2025)
Small and medium enterprises (SMEs) play a pivotal role in fostering employment opportunities and driving economic growth. Acknowledged as effective generators of employment, catalysts for the emergence of larger enterprises, and fundamental agents of national economic advancement. SMEs operate within a contemporary, dynamic, and fiercely competitive business landscape. In response, firms are compelled to devise strategic frameworks aimed at delineating sought-after competitive advantages in the market. Central to this endeavour are cost control strategies, as the optimization of expenditures directly impacts profitability. This study conducts an extensive literature review on the efficacy of cost control strategies on the performance of youth-owned SMEs in Ethiopia. It seeks to elucidate key cost control strategies, challenges inherent in their implementation within SMEs, the influence of financial literacy on SME performance, and the implications of cost control measures on SMEs performance. Ultimately, it recommends prioritizing policy interventions geared towards enhancing financial literacy among youth and providing support mechanisms for the implementation of cost control strategies within SMEs in Ethiopia.